Highly Oxygenated Dimeric Grayanane Diterpenoids as Analgesics: TRPV1 and TRPA1 Dual Antagonists from Rhododendron molle. Issue 19 (26th July 2022) - Huang, Lang; Zheng, Guijuan; Feng, Yuanyuan; Jin, Pengfei; Gao, Biao; Zhang, Hanqi; Ma, Xiaomin; Zhou, Junfei; Yao, Guangmin
Comprehensive Summary: Six highly oxygenated dimeric grayanane diterpenoids (1—6) including three new ones, bismollethers A—C (1—3), were isolated from the flowers of Rhododendron molle collected at Qichun, Hubei, China. The structures and relative configurations of 1—6 were determined by comprehensive spectroscopic data analysis and 13 C NMR calculation with DP4+ analysis. The absolute configurations of bismollethers A—C (1—3) and birhodomollein B (5) were indubitably assigned by single‐crystal X‐ray diffraction analysis, revealing the head‐to‐tail linking manner of diterpenoid monomers. Bismollether A (1) is a caged dimeric grayanane diterpenoid linked through two oxygen‐bridges of C‐2 − O − C‐14′ and C‐14 − O − C‐2′, featuring a unique 1, 8‐dioxacyclotetradecane motif. The plausible biosynthesis pathways of 1—6 are proposed. All the isolates displayed significant analgesic activities and their structure‐activity relationships were discussed. Grayanane diterpenoid dimers were found to be TRPV1 and TRPA1 dual antagonists, and docking studies provide a structural basis to design potent analgesics. Abstract : Six highly oxygenated dimeric grayanane diterpenoids (1—6) as potent analgesics were isolated from the flowers of Rhododendron molle and defined as TRPV1 and TRPA1 dual antagonists. Bismollether A (1) is a caged grayanane diterpenoid dimer linked through two oxygen‐bridges of C‐2 − O − C‐14′ and C‐14 − O − C‐2′, featuring a unique 1, 8‐dioxacyclotetradecane motif. Single‐crystal X‐ray diffraction analysis of 1—3 and 5 revealed the linking manner of two monomers and assigned their absolute configurations. This is the first time to report the crystal structures, analgesic activities, and TRPV1/TRPA1 dual analgesic targets of dimeric grayanane diterpenoids.